2016
DOI: 10.31254/jahm.2016.2204
|View full text |Cite
|
Sign up to set email alerts
|

Comparative physico-chemical validation between Arsenic-based Indian traditional drugs Haratal Bhasma and Rasamanikya

Abstract: Background: Arsenic containing drugs Rasamanikya (RM) and Haratal Bhasma (HB) are used in Ayurveda for the treatment of several ailments. They are prepared from raw Haratal (RH) by the distinct Ayurvedic procedure. Hence, proper scientific validation by physico-chemical studies is needed for their acceptability to the modern scientific community. Methods: RM and HB were prepared from RH. Namburi Phased spot test (NST) study was done to check the quality of prepared drugs. Loss on drying, extractive values, ash… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…As per a study done by P. Satadru et al, on Haritala (orpiment) Bhasma (Calx) & Rasamanikya, it has been found that wt% of arsenic in Haritala (orpiment) Bhasma (Calx) 58.69%, and sulphur is 11.69%, while in Rasamanikya wt% of arsenic is 41.77%, and sulphur is 15.81%. [23] While comparing the wt% of arsenic founds in Shilajit Bhasma (Calx) in present study, a range of 0.51-0.58% of weight of arsenic found presents (for comparison please see graph below, Graph-3).…”
Section: Graph-3mentioning
confidence: 54%
“…As per a study done by P. Satadru et al, on Haritala (orpiment) Bhasma (Calx) & Rasamanikya, it has been found that wt% of arsenic in Haritala (orpiment) Bhasma (Calx) 58.69%, and sulphur is 11.69%, while in Rasamanikya wt% of arsenic is 41.77%, and sulphur is 15.81%. [23] While comparing the wt% of arsenic founds in Shilajit Bhasma (Calx) in present study, a range of 0.51-0.58% of weight of arsenic found presents (for comparison please see graph below, Graph-3).…”
Section: Graph-3mentioning
confidence: 54%